Effect of distribution of striated laser hardening tracks on dry sliding wear resistance of biomimetic surface. (1st January 2018) - Su, Wei; Zhou, Ti; Zhang, Peng; Zhou, Hong; Li, Hui
Highlights: Striated biomimetic laser tracks were created by Nd:YAG laser. Self-regenerated hard zone was proved to be benefit in resisting abrasion. Even distributed laser tracks can stable sliding process of bionic sample. Abstract: Some biological surfaces were proved to have excellent anti-wear performance. Being inspired, Nd:YAG pulsed laser was used to create striated biomimetic laser hardening tracks on medium carbon steel samples. Dry sliding wear tests biomimetic samples were performed to investigate specific influence of distribution of laser hardening tracks on sliding wear resistance of biomimetic samples. After comparing wear weight loss of biomimetic samples, quenched sample and untreated sample, it can be suggested that the sample covered with dense laser tracks (3.5 mm spacing) has lower wear weight loss than the one covered with sparse laser tracks (4.5 mm spacing); samples distributed with only dense laser tracks or sparse laser tracks (even distribution) were proved to have better wear resistance than samples distributed with both dense and sparse tracks (uneven distribution). Wear mechanisms indicate that laser track and exposed substrate of biomimetic sample can be regarded as hard zone and soft zone respectively. Inconsecutive striated hard regions, on the one hand, can disperse load into small branches, on the other hand, will hinder sliding abrasives during wear. Soft regions with small range are beneficial in consuming mechanical energy and storing lubricative oxides, however, soft zone with large width (>0.5 mm) will be harmful to abrasion resistance of biomimetic sample because damages and material loss are more obvious on surface of soft phase. As for the reason why samples with even distributed bionic laser tracks have better wear resistance, it can be explained by the fact that even distributed laser hardening tracks can inhibit severe worn of local regions, thus sliding process can be more stable and wear extent can be alleviated as well.